On visualization of multidimensional data using three‐dimensional embedding space - Žilinskas, Antanas; Žilinskas, Julius (Technological and Economic Development of Economy, 2006)
Multidimensional scaling addresses the problem of representation of objects specified by proximity data by points in low dimensional embedding space. The problem is reduced to optimization of an accuracy measure of fit of the proximity data by the distances between the respective points. Three‐dimensional embedding space is considered in the present paper. Images of data of different dimensionality are discussed as well as dependence of visualization accuracy on dimensionality of embedding space and complexity of data.On visualization of multidimensional data using three-dimensional embedding spaceSantrauka. Daugiamatės skalės naudojamos artimumu apibrėžtiems duomenims atvaizduoti taškais mažo mato erdvėje. Uždavinys sprendžiamas optimizuojant atstumo tarp atitinkančių taškų atitikties duotiems artimumams įvertį. Vaizdavimo tikslumo priklausomybė nuo skalės ir duomenų mato yra aptarta ir pasiūlyta naudoti trimates skales. Įvairių duomenų trimatės skalės pavaizduotos projekcijomis ir aptartos.Reikšminiai žodžiai: daugiamatės skalės, globali optimizacija, metaeuristika, miesto kvartalo metrika, daugiamačių duomenų vizualizavimas.First Published Online: 21 Oct 2010